Model Aplikasi Sistem E-Commerce untuk Rekomendasi dan Pemantauan Harga Produk Penjual - Grace Levina Dewi; Brigitta Angeline; Andrew Jonathan Hadikusuma; Kevin Setiono; Mikhael Setiawan; Suhatati Tjandra; Hendrawan Armanto (STMIK Banjarbaru, 2025)
Sellers on e-commerce platforms face difficulties in determining strategic pricing due to dynamic competition. To address this problem, an integrated system application model was developed as a solution to assist sellers. This research utilized the Research and Development (R&D) methodology with a waterfall model, which included the stages of needs analysis, system design, implementation, performance verification and data analysis, and final evaluation and revision. The result is a functional application capable of providing features such as search, strategic price recommendations at three levels (lowest, average/middle, highest), viewing more detailed information about products sold in graphical form, and other features. Usability testing conducted on target users yielded average scores of 95.54% for free-type customers, 91.26% for premium-type customers, and 96.8% for buyer-type cutomers. This indicates excellent ease of use and a high level of acceptance. This website model proved to be an effective and practical tool for sellers to establish competitive pricing strategies.Keywords: E-commerce; Price Monitoring; Strategic Pricing; Research and Development; Recommender System AbstrakPenjual pada platform e-commerce menghadapi kesulitan dalam menentukan harga strategis akibat persaingan dinamis. Untuk mengatasi masalah ini, sebuah model aplikasi sistem terintegrasi dikembangkan sebagai solusi untuk membantu penjual. Penelitian ini menggunakan metodologi Research and Development (R&D) dengan waterfall yang mencakup tahap analisis kebutuhan; perancangan sistem; implementasi; verifikasi kinerja dan analisis data; dan evaluasi akhir dan revisi. Hasilnya adalah sebuah aplikasi fungsional yang mampu menyediakan fitur pencarian, rekomendasi harga strategis pada tiga level (terendah, rata-rata/menengah, tertinggi), melihat informasi lebih detail mengenai produk yang dijual dalam bentuk grafik, dan fitur lainnya. Pengujian usabilitas menggunakan usability testing terhadap target pengguna menghasilkan skor rata-rata 95,54% pada customer yang bertipe gratis, 91,26% untuk pengguna bertipe premium, dan 96,8% pengguna yang bertipe pembeli. Hal ini yang mengindikasikan kemudahan penggunaan dan tingkat penerimaan sangat baik. Model website ini terbukti menjadi alat bantu yang efektif dan praktis bagi penjual untuk menetapkan strategi harga kompetitif.